Pengembangan Model Bisnis Layanan Lumpur Tinja dengan Pendekatan Institusional : (Studi Kasus: Perumda Paljaya DKI Jakarta) - Ahmad Ramadhan Haedaryanto; Setiyawan, Ahmad Soleh (Business Perspective Journal, 2024)
Indonesia has a decent sanitation service percentage of 74.58%, including safe sanitation of 7.42%. This figure is accompanied by a high percentage of open defecation behavior, which is around 9.36%, equivalent to 25 million people, making Indonesia ranked 3rd in the world for the largest number of open defecation. Households that have access to sanitation are those that have a connection to a Waste Water Treatment System (SPAL) that is desludged and disposed of at a Fecal Sludge Treatment Plant (STP). However, of the 272 sewage treatment plants built in 2018, only 8 were operating optimally. The local government forms a regional device or institution as a service provider (operator) in the form of UPTD, BLUD, and BUMD. BUMD institutions are more sustainable than other institutions. This study aims to identify performance indicators at the DKI Jakarta BUMD Perumda Paljaya institution, identify regional potential at the DKI Jakarta BUMD Perumda Paljaya institution, and analyze the development of the DKI Jakarta BUMD Perumda Paljaya institution business model. The data collection method is using the interview method. Data analysis using the ATLAS.TI application. The results are useful for business development of DKI Jakarta BUMD Perumda Paljaya institutions. Keywords: institutions, Perumda Paljaya DKI Jakarta, regional potential, performance indicators, ATLAS.Ti, business model development